Investigating the Impact of Climate Change on Plant Phenology and Its Consequences for Ecosystem Dynamics - Jyoti (Innovative Research Thoughts, 2023)
Plant phenology and its implications for ecosystem dynamics are two areas where climate change is having a significant impact on Earth's ecosystems. This abstract is an attempt to provide a bird's eye perspective of the studies done on how climate change affects plant phenology and how that, in turn, affects the functioning of ecosystems. The study of phenology—the timing of annual life cycle events in plants and animals including blooming, leaf emergence, and migration—provides a valuable window into the effects of climate change. As average temperatures throughout the world continue to climb, changes in seasonal patterns become more noticeable. The timing of growth, reproduction, and other ecosystem dynamics in plants is altered as a result of these climatic shifts. Temperature changes, changing precipitation patterns, shifts in photoperiod, and alterations in the availability of critical resources are the principal causes of phenological shifts generated by climate change. There are complicated cascade consequences across the ecosystem because of the way these elements affect plant physiology, genetics, and community relationships. The effects of alterations in plant phenology extend to several trophic levels and ecological systems. For instance, if a plant's blooming and fruiting times are changed, it may throw off its synchrony with its pollinators or seed dispersers, leading to decreased reproductive success and new interactions across species. In addition, trophic mismatches may disrupt food webs and ecological stability when species at various trophic levels react differently to climatic signals.